Nine-year audit of post-dural puncture headache in a tertiary obstetric hospital in Singapore. (December 2016) - Tien, J.C.; Lim, M.J.; Leong, W.L.; Lew, E.
Highlights: Post-dural puncture headache and associated event rate is 0.15% with a downward trend. More dural punctures occurred out of office hours and with junior anesthesiologists. Management of post-dural puncture headache was varied. Epidural blood patch was infrequently performed. Abstract: Background: The KK Women's and Children's Hospital is a tertiary obstetric unit with approximately 11 000 deliveries per year. Epidural analgesia is used in about 40% of laboring women. We reviewed the incidence and management of post-dural puncture headache over a nine-year period. Methods: A retrospective audit of labor epidural analgesia database records from 1 June 2005 to 31 May 2014 was conducted, identifying an "event" as an accidental dural puncture, an inadvertent intrathecal catheter insertion and/or development of a post-dural puncture headache. Results: A total of 43 434 epidural records were reviewed. Sixty-three events were identified (an incidence of 0.15%). Women had median age of 30 years and median body mass index of 27.6 kg/m 2 ; 69.8% (44/63) delivered vaginally. Procedures performed by less experienced anesthesiologists and those performed outside office hours were associated with a higher incidence of accidental dural puncture. An intrathecal catheter was inserted in 52 of 58 women (89.7%). Headache developed in 24 of 38 (63.1%) women in whom there was a witnessed accidental dural puncture. Most women who developed post-dural puncture headache presented during the primary admission (36/39; 92.3%). Paracetamol and non-steroidal anti-inflammatory drugs were the most commonly prescribed medications. Six women (9.5%) received an epidural blood patch which led to resolution of headache. Conclusion: A retrospective audit over a nine-year period at a tertiary teaching hospital found the overall incidence of post-dural puncture headache and associated events to be 0.15%, with a decreasing trend coinciding with improvement in the teaching and supervision of trainees in labor epidural procedures.